2022
DOI: 10.1021/acscatal.2c01700
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Tandem CO2–Ethane Reactions and Hydroformylation for C3 Oxygenate Production

Abstract: The strategy of the tandem hydroformylation reaction for C3 oxygenate production from CO2 and ethane represents an opportunity to simultaneously upgrade greenhouse gas CO2 and the large-reserved shale gas into value-added liquid products. One of the challenges is how to tune and achieve the appropriate ethylene/CO/H2 ratios for the downstream hydroformylation. Herein, we analyze and identify the desired ethylene/CO/H2 ratios by considering different combinations of main and side reactions of CO2 and ethane, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…4), one can roughly estimate the corresponding C 2 H 4 selectivity from CO 2 -activation of C 2 H 6 over a bimetallic system, simply using the DFT-calculated values for the two descriptors, reactive oxygen binding energy and alloy surface formation energy. Accordingly, the C 2 H 4 selectivity measured previously for bimetallic-derived systems, such as NiFe 3 (experiment: 78% 16 vs. descriptor-based estimation: ∼75%), PdFe 3 (86% 23 vs. ∼85%), PtCo 3 (1% 13 vs. ∼0%), PtNi 3 (1% 18,19 vs. ∼0%), and PtSn 3 (83% 36 vs. ∼75%) can be estimated, which reproduced the experimental values reasonably well. Therefore, the DFT-calculated formation energies of alloy surfaces and the reactive oxygen binding energies can be used as universal descriptors to screen the bimetallic-derived catalysts for the selective activation of C 2 H 6 with CO 2 .…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…4), one can roughly estimate the corresponding C 2 H 4 selectivity from CO 2 -activation of C 2 H 6 over a bimetallic system, simply using the DFT-calculated values for the two descriptors, reactive oxygen binding energy and alloy surface formation energy. Accordingly, the C 2 H 4 selectivity measured previously for bimetallic-derived systems, such as NiFe 3 (experiment: 78% 16 vs. descriptor-based estimation: ∼75%), PdFe 3 (86% 23 vs. ∼85%), PtCo 3 (1% 13 vs. ∼0%), PtNi 3 (1% 18,19 vs. ∼0%), and PtSn 3 (83% 36 vs. ∼75%) can be estimated, which reproduced the experimental values reasonably well. Therefore, the DFT-calculated formation energies of alloy surfaces and the reactive oxygen binding energies can be used as universal descriptors to screen the bimetallic-derived catalysts for the selective activation of C 2 H 6 with CO 2 .…”
Section: Resultssupporting
confidence: 80%
“…We note here that only the reaction energies for the elementary steps involved were calculated, by assuming a BEPlike correlation between the reaction energy and the corresponding activation barrier according to our previous DFT studies on the activation of light alkanes with CO 2 . 24,36 On…”
Section: Mechanistic Understanding Using Dft Calculationsmentioning
confidence: 99%
“…Thus, it is critical to reduce the temperature in the first reactor to enable a completely catalytic tandem process, in which the C 2 H 4 /CO/H 2 ratios can be better tuned via the selection of appropriate catalysts. Xie et al recently analyzed and identified the desired C 2 H 4 /CO/H 2 ratios by considering different combinations of main and side reactions of CO 2 and ethane . To obtain a C 2 H 4 /CO/H 2 ratio that is close to the typical feed ratio (1/1/1) for the subsequent hydroformylation, the analysis showed that the desired catalysts for the first reactor should enable multiple simultaneous reactions of direct dehydrogenation of ethane (DDHE), ODHE, DRE, and RWGS: i.e., either ODHE + DDHE + DRE (theoretical product ratio of 1/1/0.88) or DDHE + RWGS + DRE (theoretical product ratio of 1/1.15/1).…”
Section: Tandem Reaction Strategies For the Production Of C3 Oxygenat...mentioning
confidence: 99%
“…24 In the tandem configuration with PtSn 3 /γ-Al 2 O 3 catalyst at 600 °C in the first reactor, the obtained C 3 Oxy productivity was comparable to that of the aforementioned Fe 3 Ni 1 /CeO 2 catalyst at 750 °C (Figure 3g). 10 2.1.2. Plasma−Thermocatalytic Scheme (P-TC).…”
Section: Thermocatalytic−thermocatalytic Scheme (Tc-tc)mentioning
confidence: 99%
See 1 more Smart Citation